Flood-Irrigated Ridge-Till Corn Cost-Return Budget - Dumler, Troy J.; O'Brien, Daniel M. (My University, 1999)
This publication provides expected yields and enterprise return for producing flood-irrigated corn under a ridge-till cropping system.
MF969_1999_10
Keywords: MF969; Economics; Crops; MF